2019
DOI: 10.1542/neo.20-1-e25
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Digestion and Absorption in the Preterm Infant

Abstract: The human fetus receives oral nutrition through swallowed amniotic fluid and this makes a significant nutritional contribution to the fetus. Postnatally, macronutrient absorption and digestion appear to function well in the preterm infant. Although pancreatic function is relatively poor, the newborn infant has several mechanisms to overcome this. These include a range of digestive enzymes in human milk, novel digestive enzymes involved in fat and protein digestion that do not appear to be present in the older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 88 publications
1
2
0
3
Order By: Relevance
“…Food allergy was not common in children with asthma/ALS due to the facts that food allergens did not affect the respiratory tract system directly. We also found that the positive rate of food allergens was higher in the infantile period than that in other periods, which may be due to that the digestive enzymes were not mature and the infants needs to adapt to various food patterns in this period [13]. On the other hand, the most common aeroallergens were DF and HDM, which was consistent with the epidemiological findings that mites were the most common allergens in China [14].…”
Section: Discusssionsupporting
confidence: 85%
“…Food allergy was not common in children with asthma/ALS due to the facts that food allergens did not affect the respiratory tract system directly. We also found that the positive rate of food allergens was higher in the infantile period than that in other periods, which may be due to that the digestive enzymes were not mature and the infants needs to adapt to various food patterns in this period [13]. On the other hand, the most common aeroallergens were DF and HDM, which was consistent with the epidemiological findings that mites were the most common allergens in China [14].…”
Section: Discusssionsupporting
confidence: 85%
“…Favorecer un adecuado crecimiento en los niños con BPN: nutrición óptima 1.1 Definición de nutrición óptima La nutrición óptima para el neonato se ha definido como aquella que da lugar a un crecimiento y un desarrollo adecuados, sin exceder sus capacidades metabólicas y excretoras. El Comité de Nutrición de la Academia Americana de Pediatría (AAP) recomienda que el objetivo de la nutrición debe ser lograr un crecimiento posnatal adecuado a la edad gestacional, definido no solo por los parámetros antropométricos, sino también por la variación de la composición corporal y la retención de los diferentes nutrientes [24].…”
Section: Orientación Y Educación a Padres Y Cuidadores Con Niños Con ...unclassified
“…Actualmente no existen recomendaciones basadas en la evidencia para preservar la salud renal de los niños con BPN a largo plazo. Las siguientes recomendaciones se hacen según la revisión de recomendaciones que han hecho grupos de expertos en el mundo para el seguimiento de los niños con BPN [4,16,19,24,73,89,90,120,121].…”
Section: Componentes De La Estrategiaunclassified
“…While enteral feeds arguably begin by 20 weeks of gestation with fetal swallowing [73], the digestive tract of infants only reaches functional maturity between three and six months of age [74]. In the weeks following birth, infants must transition from a metabolism heavily predicated on placental transfer of maternal glucose to one more inclusive of dietary lipids, ideally sourced from maternal HM [75]. Low pancreatic enzyme and bile salt concentrations during the neonatal period can present nutritional challenges [76], especially if the infant requires formula feeding, but HM provides essential digestive enzymes the infant lacks in order to increase lipid absorption in the developing neonate.…”
Section: Digestion Of Milk Fat Globules In Term and Preterm Infantsmentioning
confidence: 99%
“…In the stomach, pepsin and gastric lipase begin digestion of the MFG. Pepsin, due to an optimal working pH of 2, is both less active and abundant in preterm infants than in term infants or adults [75]. However, a longer period of gastric digestion provided by immature gastrointestinal motility, potentially in combination with additional undescribed proteases active in the preterm stomach [81], appears to compensate for this lower proteolytic capability [82].…”
Section: Digestion Of Milk Fat Globules In Term and Preterm Infantsmentioning
confidence: 99%